The Chemistry of Devotion: Materials, Techniques, and Symbolism in Ethiopian Sacred Metalwork and Manuscript Illumination - Belay Sitotaw Goshu; Muhammad Ridwan (Lakhomi Journal Scientific Journal of Culture, 2026)
Ethiopian sacred arts represent one of the world's oldest continuous traditions of material and spiritual transformation, yet the chemical knowledge embedded in these practices remains largely unexplored in the historiography of science and art history. Purpose: This study examines Ethiopian sacred metalwork and manuscript illumination as a form of applied alchemy, investigating the practical chemistry, techniques, and theological symbolism underlying these traditions. Drawing on interdisciplinary approaches combining archaeometric analysis (X-ray fluorescence spectroscopy, Raman spectroscopy, Fourier Transform Infrared Spectroscopy, and Pyrolysis-Gas Chromatography–Mass Spectrometry), art historical examination, ethnographic documentation, and textual analysis, this study synthesizes existing research and presents new interpretations of Ethiopian sacred material culture. Ethiopian artisans possessed sophisticated indigenous chemical knowledge encompassing metallurgy (smelting, lost-wax casting, alloying, gilding), parchment-making, ink preparation (carbon-based and iron-gall inks), and pigment production (mineral, plant-based, and imported pigments). This practical chemistry was deeply intertwined with theological symbolism: gold signified divine light, red represented the blood of Christ, and the processes of transformation were understood as acts of purification and devotion. The Ethiopian tradition, continuous since late Antiquity, serves as a vital source for understanding vanished historical practices. Ethiopian sacred arts constitute a distinctive tradition of applied alchemy that challenges Eurocentric narratives of chemical knowledge, demonstrating that sophisticated material practices flourished in non-European contexts. Future research should prioritize systematic chemical analysis of wider manuscript and metal object corpora, ethnographic studies of living craftspeople, comparative studies with other African and Eastern Christian traditions, and digital humanities approaches to preserve and analyze this endangered heritage.